RNA-Seq of Tomato Fruit-Alternaria Chitin Oligomer Interaction Reveals Genes Encoding Chitin Membrane Receptors and the Activation of the Defense Response - Yaima Henry García; Rosalba Troncoso-Rojas; María Elena Báez-Flores; Miguel Ángel Hernández-Oñate; Martín Ernesto Tiznado-Hernández (Horticulturae, 2023)
The tomato is an economically important crop worldwide, although fungal infections by Alternaria alternata are the main cause of large postharvest fruit losses. One alternative to chemical control is the induction of the defense mechanism of plants with natural molecules such as chitin. Chitin is a polysaccharide of the fungal cell wall that is recognized by plasma membrane receptors that activates the transcription of plant defense genes. Because there is little information on the genes involved in chitin perception and defense responses to fungal chitin oligomers in tomato fruits, the main objective of this study was to identify pattern recognition receptor-associated genes in tomato fruits that perceive chitin oligomers from the necrotrophic fungus A. alternata using RNA-Seq. Chitin oligomers were obtained from A. alternata via enzymatic treatment. Tomato fruits in the pink ripening stage were exposed to these chitin oligomers for 30 min. The induction of tomato genes encoding a plasma membrane receptor that recognizes fungal chitin (LRR, RLK, SlLYK4, and SlCERK1) was observed 30 min after treatment. Similarly, the perception of Alternaria chitin oligomers triggered the induction of genes involved in signaling pathways regulated by ethylene and jasmonic acid. Further, activation of plant defense phenomena was confirmed by the upregulation of several genes encoding pathogenesis-related proteins. The scientific information generated in the present work will help to better elucidate tomato fruit’s response to pathogens and to design protocols to reduce postharvest losses due to fungal infection.